Occurrence of antibiotics in pharmaceutical industrial wastewater, wastewater treatment plant and sea waters in Tunisia - Tahrani, Leyla; Van Loco, Joris; Ben Mansour, Hedi; Reyns, Tim (Journal of water and health, 2016)
Antibiotics are among the most commonly used group of pharmaceuticals in human medicine. They can therefore reach surface and groundwater bodies through different routes, such as wastewater treatment plant effluents, surface runoff, or infiltration of water used for agricultural purposes. It is well known that antibiotics pose a significant risk to environmental and human health, even at low concentrations. The aim of the present study was to evaluate the presence of aminoglycosides and phenicol antibiotics in municipal wastewaters, sea water and pharmaceutical effluents in Tunisia. All analysed water samples contained detectable levels of aminoglycoside and phenicol antibiotics. The highest concentrations in wastewater influents were observed for neomycin and kanamycin B (16.4ng mL−1 and 7.5 ng mL−1, respectively). Chloramphenicol was found in wastewater influents up to 3 ng mL−1. It was observed that the waste water treatment plants were not efficient in completely removing these antibiotics. Chloramphenicol and florfenicol were found in sea water samples near aquaculture sites at levels up to, respectively, 15.6 ng mL−1 and 18.4 ng mL−1. Also aminoglycoside antibiotics were found near aquaculture sites with the highest concentration of 3.4 ng mL−1 for streptomycin. In pharmaceutical effluents, only gentamycin was found at concentrations up to 19 ng mL−1 over a sampling period of four months.